(untitled) (Fiep Bulletin - online, 2019)
New technologies invade the school walls and permeate the actions of the students. The theme of this research was:The Physical Education and the list of traditional games and new technologies. We justify this choice because we believe that youdo not need leave to work with the traditional games to take place only and exclusively the technological tricks. From the followingquestion: Is it possible to work with traditional games while new games and technological? This work aimed to rescue thecontributions of traditional games in child development and to study the influences of new technologies. The research wasclassified as literature. The authors point out that both the traditional games handed down from generation to generation as thenew games, electronic games, mobile phones, tablets and video games, can inhabit the school environment. Moving betweenthese possibilities is the child who wants to play, even then we believe that children have lost interest in the old ways of playingover a new technological way, both have value and should have space in the school environment.